Pengaruh Budaya Organisasi Terhadap Motivasi dan Kepuasan Kerja Serta Kinerja Karyawan (Pada Batik Benang Raja Surabaya) - Eko Winarni; Ali Mahsun (Fakultas Ekonomi Universitas Yos Soedarso, 2022)
The purpose of this study is to determine how much influence Organizational Culture has on Motivation, Job Satisfaction and Employee Performance. The variables used in this research are organizational culture, motivation as the independent variable, employee performance as the dependent variable, job satisfaction as the intervening variable. The unit of analysis is Batik Yarn Raja Surabaya employees. The population in this study amounted to 117 employees with a sample of 100 respondents. The analysis technique used is the Structural Equation Model (SEM). The results in this study are Organizational Culture has a positive effect on Motivation by 0.499, Organizational culture has a positive effect on Job Satisfaction by 0.365, Motivation has a positive effect on Job Satisfaction by 0.325, Organizational Culture has a positive effect on Performance by 0.305, Motivation has a positive effect on Performance by 0.352, and Job satisfaction has a positive effect on performance of 0.519. The results of this study can be used by subsequent researchers, as a reference to enable future researchers.